Pausas na interpretação teatral: delimitação de constituintes prosódicos - Jurado Filho, Lourenço Chacon [UNESP] (2014)
We intend to observe the function of a linguistic resource – the pause – in theatrical interpretation. Connected to the field of speech therapy, we search for theoretical support in the Linguistics field, mainly in prosodic phonology – specifically, we highlight intonational phrase and phonological utterance, prosodic constituents –, proposing a dialogue between these fields, regarding the work with actors. In speech therapy literature, the work with actors focuses, centrally, in organic issues involved in the vocal process, such as “misuse” or “voice abuse”. To a smaller extent, we find, in this literature, researches that emphasize issues regarding interpretation and expressive resources, besides a few emphasizing the importance of linguistic resources in interpretation. Differently, in linguistics literature, the pause is approached, to a larger extent, from the phonetic perspective, related to several language levels. In this research, we analyzed audio recordings of four actors from a same theatrical group, acting the theatrical text Brutas flores, focused on these aims: (1) detect the place where pauses happen in the interpretation of a single text by four actors; (2) survey physical characteristics of length of these pauses; (3) check to what extent the length of a pause is related to the place where it happens, regarding the prosodic limits of intonational phrases (I) and phonological utterance (U). We could observe that, although the interpretation is characterized by the subjectivity of the actor, the interpretation is constructed based in the possibilities offered by the prosodic organization of the text itself, being more or less flexible.We were also able to confirm, by considering the length of VVs units containing pauses, the prosodic hierarchy proposed by Nespor & Vogel, once the length of these units in U's limits was significantly higher than the length in I's limits. Thus, our results reinforce the premise that a linguistic structure overlaps the subjectivity of the actor, i. e., the premise that the strength of linguistic structure organization acts on the possible individual operation/style.